Pancreas–Kidney transplantation: Impact of dialysis modality on the outcome. (8th April 2015) - Martins, La Salete; Malheiro, Jorge; Pedroso, Sofia; Almeida, Manuela; Dias, Leonidio; Henriques, António C.; Silva, Donzília; Davide, José; Cabrita, António; Noronha, Irene L; Rodrigues, Anabela
Summary It remains controversial whether dialysis modality prior to SPKT (simultaneous pancreas–kidney transplantation) affects the outcome. We analyzed outcomes in type 1 diabetic patients undergoing SPKT, comparing peritoneal dialysis (PD) and hemodialysis (HD) groups: 119 had been on HD; 39 on PD. They were comparable except regarding dialysis time, higher in HD patients (30 ± 23 vs. 21 ± 15 months, P = 0.003). Thrombosis‐driven relaparotomy was more frequent in PD patients (12.8% vs. 1.7%, P = 0.014). Pancreas loss due to infection was higher in PD patients (12.8% vs. 3.4%, P = 0.042). Thrombosis‐related kidney loss was more frequent in PD patients (5.1%, vs. 0% in HD patients, P = 0.058). Thirteen deaths occurred, more within the PD group (17.9% vs. 5%; P = 0.011), being infection the leading cause (13.5%, vs. 1.7% in HD patients, P = 0.010). Patient survival was inferior in PD patients. Besides PD, cardiovascular disease and graft failure were independent predictors of patient death. In conclusion, PD patients more frequently complicated with intra‐abominal infection leading to pancreatic loss and with renal thrombosis, with adverse impact on survival. As a PD first strategy in end‐stage renal disease patients is generally associated with good outcomes, these gloomier results after SPKT urge for careful adjustment of infection and thrombosis prophylactic protocols in PD patients.